Histologic findings associated with laser interstitial thermotherapy for glioblastoma multiforme - J. Bradley Elder; Kristin Huntoon; Jose Otero; Behiye Kaya; Jeff Hatef; Mostafa Eltobgy; Russell R. Lonser (BMC, 2019)
Abstract Background Laser-interstitial thermal therapy (LITT) has been supported by some authors as an ablative treatment of glioblastoma multiforme (GBM). Although the effects of LITT have been modeled in vivo, the histologic effects in a clinical circumstance have not been described. We analyzed tissue from a patient who underwent LITT as primary treatment for GBM. Case presentation A 62-year-old male was diagnosed with a left temporal GBM and underwent LITT at an outside institution. Despite corticosteroid therapy, the patient was referred with increasing headache and acalculia associated with progressive peritumoral edema two weeks after LITT procedure. En bloc resection of the enhancing lesion and adjacent temporal lobe was performed with steroid-independent symptom resolution (follow-up, > 2 years). Histologic analysis revealed three distinct histologic zones concentrically radiating from the center of the treatment site. An acellular central region of necrosis (Zone 1) was surrounded by a rim of granulation tissue with macrophages (CD68) (Zone 2; mean thickness, 1.3 ± 0.3 mm [±S.D.]). Viable tumor cells (identified by Ki-67, p53 and Olig2 immunohistochemistry) were found (Zone 3) immediately adjacent to granulation tissue. The histologic volume of thermal tissue ablation/granulation was consistent with preoperative (pre-resection) magnetic resonance (MR)-imaging. Conclusion These findings are the first in vivo in humans to reveal that LITT causes a defined pattern of tissue necrosis, concentric destruction of tumor and tissue with viable tumor cells just beyond the zones of central necrosis and granulation. Furthermore, MR-imaging appears to be an accurate surrogate of tissue/tumor ablation in the early period (2 weeks) post-LITT treatment. Surgery is an effective strategy for patients with post-LITT swelling which does not respond to steroids.